Non-linear connections between maternal hemoglobin during the third trimester of pregnancy and birth weight outcomes in full-term newborns: Estimating the breakpoints - Xie, Guilan; Wang, Ruiqi; Zhang, Boxing; Sun, Landi; Xiang, Wanwan; Xu, Mengmeng; Zhu, Sijing; Guo, Leqian; Xu, Xu; Yang, Wenfang (Frontiers in Nutrition, 2022)
Anemia is still an unfinished global health problem and adverse birth weight outcomes have everlasting influences on the health of later life. However, the non-linear connections and breakpoints of maternal hemoglobin with birth weight outcomes are still needed to be further elucidated.We aimed to reveal the non-linear connections between maternal hemoglobin during the third trimester of pregnancy and birth weight, low birth weight(LBW), macrosomia, small for gestational age(SGA), and large for gestational age(LGA) in full-term newborns, and elucidate the breakpoints of the connections. A total of 11,411 singleton, full-term, and live newborns, whose mothers conducted the examination of hemoglobin concentration before delivery, were included in this study.Generalized additive model was used to identify and visualize the non-linear connections between maternal hemoglobin and birth weight outcomes.Piecewise linear regression model was adopted to estimate the breakpoints of the connections and report the non-linear connections in detail. There were inversed “U” shaped exposure-response connections between maternal hemoglobin concentration and birth weight and the risk of macrosomia. There was an increased trend of the risk of LBW and a decreased trend of LGA with the rise of maternal hemoglobin concentration.The breakpoints of maternal hemoglobin for birth weight were 100g/L and 138g/L, and those for SGA were 97g/L and 138g/L.The breakpoints of maternal hemoglobin were 119g/L for LBW, 105g/L for macrosomia, and 106g/L for LGA. When maternal hemoglobin concentration ranged from 100g/L to 138g/L, maternal hemoglobin concentration increased per 1g/L, birth weight significantly decreased 2.58g(95%CI:–3.33,–1.83). When maternal hemoglobin concentration ranged from 97g/L to 138g/L, maternal hemoglobin concentration increased per 1g/L, the risk of SGA significantly increased 2%(95%CI:1%,3%). When maternal hemoglobin concentration was equal to or lower than 119g/L, maternal hemoglobin concentration increased per 1g/L, the risk of LBW significantly increased 3%(95%CI:0%,5%). When maternal hemoglobin concentration was higher than the breakpoints, the risks of macrosomia(OR=0.99,95%CI:0.98,0.99) and LGA(OR=0.99,95%CI:0.98,1.00) declined as the increase of maternal hemoglobin concentration.There were non-linear connections between maternal hemoglobin and birth weight outcomes, and there are breakpoints in the connections.Cost-effective interventions targeting pregnant women in prevention of abnormal maternal hemoglobin concentration should be taken to reduce the incidence of adverse birth weight outcomes.